Study of Power Parameters of Forming Profile Elliptical Screw Workpieces - Lyashuk, Oleg; Diachun, Andrii; Ðšuchvara, Ivan; Vovk, Yuriy; Dzyura, Volodymyr (International Journal of Integrated Engineering, 2021)
Based on the power-saving technologies, the design of an installation for coiling elliptical screw workpieces is worked out. Theoretical dependences for determining power and structural parameters of coiling a screw profile workpiece (SPW) on the elliptical mandrel are developed with consideration of the material grade specification and the parameters of technological equipment. The dependences of the moment value of SPW bending to the elliptical mandrel on its rotation angle, thickness and width are defined. The challenge is to develop the progressive methods of manufacturing augers and their sub-type - L-shaped auger spirals (LSAS) with high precision geometrical dimensions Computer simulation of the tape workpiece winding process on ellipse mandrel with initial conditions, displacements, deformations and stresses that arising in the material of tape workpice after applying the simulated efforts to it, was shown. Given simulation showed ranges where maximum stresses of tension and compression arising in material of tape workpiece, and made it possible to determine the minimum radius of curvature during winding, which is advisable to take at least 20 mm.